Structures and bonding of homoleptic bis(2,3-dihydro-1,3-diborole) complexes of nickel and platinum - Wadepohl, Hubert; Krüger, Carl; Siebert, Walter (Journal of organometallic chemistry, 2015)
Homoleptic metal complexes of the boron heterocycle 2,3-dihydro-1,3-diborole {(R1C)2(R2B)2R3(H)C} 1 are described. X-Ray crystal structure determinations of two nickel and platinum derivatives are presented. In the nickel complex [Ni(1d)2] 6d (R1 = R2 = R3 = Et) the essentially coplanar heterocycles attain a pentahapto coordination mode with a gauche orientation with respect to one another. An 18 VE count is attained. In contrast, in the 14 VE platinum complex [Pt(1a)2] 4a (R1 = R2 = Et, R3 = Me) the ligands are strongly folded and adopt a tetrahapto coordination. The molecule is centrosymmetric in the crystalline state. DFT MO calculations are presented to establish the relative stabilities of these coordination modes for nickel and platinum, respectively.